Diaclean - Eco friendly product for kidney disease patient - Nor Salwana, Mohammad Idris (2017)
It is an outstanding achievement for UMP researchers when they succeeded in producing synthetic kidney filter cleansing product to be used in hemodialysis process. Known as Diaclean, it is an eco-friendly cost saving product suitable for all types of dialysis. Adding up to its outstanding achievement, Diaclean has won gold medal and Best of the Best Award in Creation, Innovation & Research Exposition 2012 (CITREx’ 12).